1977
DOI: 10.1093/bja/49.10.965
|View full text |Cite
|
Sign up to set email alerts
|

OPTIMUM HUMIDIFICATION OF AIR ADMINISTERED TO A TRACHEOSTOMY IN DOGS: Scanning electron microscopy and surfactant studies

Abstract: The effect of the inhalation of dried (less than 40% water-saturation) or humidified air (100% water-saturation at 25, 30, 35 and 40 degrees C) was studied in dogs in which a tracheostomy had been performed to determine the optimal humidity. After inhalation for various periods, the dogs were killed and pieces of lung tissue were excised for analysis of surfactant. Sections of the trachea and the primary to tertiary bronchi were taken for scanning electron microscopic examination. Structural changes were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 20 publications
1
26
1
3
Order By: Relevance
“…Clinicians should be cautious as there is limited clinical experience with such conditions of humidification, which could lead to increased secretions and micro-atelectasis, as has been described in animals. 34,35 In conclusion, the humidification performance of passive, performing, hygroscopic and hydrophobic HMEs, and of active HMEs is not influenced by minute ventilation in the conditions tested in the present study, and ambient temperature has only a negligible influence. These systems are stable over a range of tested external conditions, and there is no reason to avoid their use in the case of high ambient temperature or in the case of high minute ventilation.…”
Section: Discussionmentioning
confidence: 45%
“…Clinicians should be cautious as there is limited clinical experience with such conditions of humidification, which could lead to increased secretions and micro-atelectasis, as has been described in animals. 34,35 In conclusion, the humidification performance of passive, performing, hygroscopic and hydrophobic HMEs, and of active HMEs is not influenced by minute ventilation in the conditions tested in the present study, and ambient temperature has only a negligible influence. These systems are stable over a range of tested external conditions, and there is no reason to avoid their use in the case of high ambient temperature or in the case of high minute ventilation.…”
Section: Discussionmentioning
confidence: 45%
“…However, subjects who received humidification therapy during mechanical ventilation did not present with any significant changes to their epithelial cell structure. Previous studies 29,30 showed that, during general anesthesia, the delivery of cold, dry gas into the lower respiratory tract resulted in pulmonary surfactant changes, increased pulmonary surface tension, and alveolar collapse. Based on the data presented in this report, we recommend that patients receiving general anesthesia also receive humidification therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Os autores observaram que o sistema respirató-rio sem absorvedor e com alto fluxo de gases frescos mostrou valores significativamente menores da umidade relativa (entre 37% a 39%) e absoluta (entre 8 a 9 mg H 2 O.L -1 ) do que o grupo com baixo fluxo e absorvedor de CO 2 , quando a umidade relativa ficou ao redor de 75% a 79% e a umidade abso- , mas, em nossa opinião, o menor limite de umidificação durante a anestesia é difícil de determinar 1 , porque ele depende da duração da anestesia, das condições pulmonares prévias do paciente e do sistema respiratório empregado. Os estudos referentes à umidificação foram feitos especialmente em animais de laboratório 8, [32][33][34][35] . Investigações no homem são limitadas pelo pequeno número de pacientes envolvidos em cada pesquisa e a ausência de informações sobre os pacientes envolvidos em cada estudo 2,17 .…”
Section: Discussionunclassified
“…, but, in our opinion, it is difficult to determine the lowest humidification limit during anesthesia 1 because it depends on anesthesia duration, previous pulmonary conditions and the respiratory system used. Humidification studies were primarily performed with animals 8, [32][33][34][35] . In men, investigations are limited by the small number of patients involved and the lack of information about patients involved in each study 2,17 .…”
Section: Discussionmentioning
confidence: 99%